Conceptual Change Strategies to Remediation Chemistry Students’ Misconceptions: A Literature Review - Dhini Ainul Fithrotinnisa; Rosalina Eka Permatasari (Proceeding of International Joint Conference on UNESA, 2025)
Misconceptions are a common problem in chemistry learning, both among students and college students, which can hinder the process of conceptual understanding. This study aims to assess the effectiveness of the Conceptual Change strategy in reducing misconceptions among chemistry students. The research method used was a literature review by examining five national articles published in the last five years with the subject of chemistry education students. The results of the study indicate that the Conceptual Change strategy is effective in reducing misconceptions through various models and approaches. The Conceptual Change model combined with the Three Scientific Questions (CCM-EWTQ) has been proven to be able to help students identify and correct misconceptions on the concept of acid-base indicators. The integration of the Conceptual Change strategy with the recall process also produces positive impacts in the form of increased cognitive conflict, strengthening long-term memory, and reducing the burden of misconceptions. In addition, the development of LKPD and software based on Conceptual Change shows a high level of validity, practicality, and effectiveness in helping shift conceptions from misconceptions to conceptual understanding. A key finding of this study is that Conceptual Change not only functions as a remediation strategy but also plays a role in restructuring conceptual knowledge, strengthening memory, and developing students’ critical and scientific thinking skills. Therefore, the Conceptual Change strategy is relevant for improving the quality of chemistry learning in higher education.